The effects of graphene and mesenchymal stem cells in cutaneous wound healing and their putative action mechanism - Lasocka, Iwona (Int J Nanomedicine, 2019)
This study provides a review of the therapeutic potential of graphene dressing scaffolds and mesenchymal stem cells (MSCs) and their synergistic effects with respect to cutaneous wound healing. This study also considers their putative action mechanism based on the antibacterial, immunomodulating, angiogenic, matrix remodeling effects of materials belonging to the graphene family and MSCs during the wound healing process. In addition, this study discusses the cytocompatibility of graphene, its uses as a platform for skin substitutes, the properties it possesses with respect to providing protection against microbial invasion as well as strategies aimed at minimizing the chance of the occurrence of sepsis. MSCs are capable of secreting several factors that exert a therapeutic impact on reparative processes and tissue regeneration. In light of experiments conducted to date, graphene combined with MSCs appears to have the potential to enhance both the wound healing process and infection control at the injury site.